Thermal aging coupled with cyclic fatigue in cross-linked polymers: Constitutive modeling & FE implementation. (1st October 2022) - Bahrololoumi, Amir; Shaafaey, Mamoon; Ayoub, Georges; Dargazany, Roozbeh
Abstract: A micro-mechanical constitutive model is presented to predict the concurrent effects of thermal aging and cyclic fatigue on the constitutive behavior of cross-linked polymers. The damage associated to each of those aging conditions is induced by mechanisms that have been extensively studied individually. Here, the main goal was to model the damage accumulated when those mechanisms work in parallel. In this respect, we modeled the effect of each aging condition separately through their corresponding aging mechanisms and then coupled them using the concept of network alteration platform. Accordingly, kinetic equations describing damage of each aging-mechanisms are coupled into the network alteration modular concept to allow consideration of mechanical and environmental damages synergies on the constitutive response of the polymer matrix. Following our recent models of thermal-oxidative aging, cyclic fatigue, and damage accumulation a model is developed based on the assumption of the full independence of mechanical and environmental damages. The model is implemented into finite element simulations. For validation, the devised model is bench-marked against a comprehensive set of experimental data. The proposed model shows promising results with reasonable precision.